Entomofauna visitante de Belamcanda chinensis (L.) DC (Iridaceae) durante o período de floração - Vitali, Maria de Jesus [UNESP]; Dutra, João Clovis Stanzani [UNESP]; Machado, Vera Lígia Letízio [UNESP] (Sociedade Brasileira de Zoologia, 1995)
A study of the reproductive biology of B. chinensis (L.) DC. (Iridaceae) was realized comprising floral biology and breeding systems. The floral biology studies included analyses of nectar production, occurence of osmophores, corolla pigments, ultraviolet reflexion and absortion patterns, viability of pollen, pollinators and flower visitors. The breeding systems were studied taking into account the results of manual pollinators tests. B. chinensis is self-compatible bul cross-pollination is more frequent. The effective pollinators are Plebeia droryana (Friese, 1906) (45,7%), Trigona spinipes (Fabricius, 1793) (27,3%), Tetragonisca angustula (Latreille, 1811) (9,3%). Others insects visitors are considered nectar and pollen thieves. The flowering begins generally in January and February. The complete reproductive cicle, as here considered, begining with floral bud production ending with development of mature fruits, lasts January to June. Seed dispersion is ornitocoric.
Flowering entomofauna Belamcanda chinensis (L.) DC. (Iridaceae) during flowering time
Keywords: Belamcanda chinensis; pollination; insect visitors; floral biology; reproductive biology